(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Through genre structure analysis of the Television´s Zagreb First Channel schedule from the beginning of 1970´s till the end of the 1980´s accompanied by analysis of advertising in same period, the paper will examine the ways and intensity of commercialization entrance in Croatian media space dominated then by state media. Television schedule genre change and the broadcast of economic propaganda program will point out the different character of the television. It can be said that it will serve for preparing the public for commercialization entrance and guidance of structural media space towards its fusion with advertising one. The assumption is that in spite of the TV schedule change, which was in economic sense accompanied by economy reforms in order to establish market economy, the public wasn´t yet delivered to advertisers. One of the clarification lies in the role of the media, which then had revolutionary function with main purpose of not the voters’ generation but only to create patriots. The paper will reproduce a kind of public transformation genesis from latent status in state guided media system to same status of latent consumers in dual media model. Keywords: Public, Commercialization, Genres, Television schedule, Advertising